المسجد العتيق بحي الزاوية الرباح دوره الدعوي والتعليمي - عوينات, خلود; بوديسة, سليمة; غنبازي, مطيرة; غريبي, وئام (جامعة الوادي university of eloued, 2019)
لقد تناولنا في درإسة هذإ إلبحث مفهوم إلمسجد وإلدعوة وإلتعليم و أ أهميتهم, فتطرقنا أ أيضا إلى ذكر أ أقدم إلمساجد في وإدي سوف, وبيان نشاطاتها إلدعوية, كما تكلمنا عن إلم سجد إلعتيق حي إلزإوية بالرباح, وذكر دوره إلدعوي وإلتعليم من خلال إلدروس وإلخطب, وذكرنا أ أهم إ أ لئمة إلذين توإلوإ على إمامة إلمسجد وخدمته, وتحدثنا عن تعليم إلقرأآن إلكريم, وذكر بعض إلطلبة إلذين تخرجوإ وبعض من نماذج إلخطب إلتي أ ألقاها أ أئمة إلمسجد. Research Summary : In the study of this research, we discussed the concept of the mosque, the call and the importance of education. We also referred to the mention of the oldest mosques in Wadi Suf and its activities. We also talked about the ancient mosque in Al-Zawahah neighborhood. On the imam of the mosque and his service, and talked about the teaching of the Koran, and mentioned some students who graduated and some of the examples of speeches delivered by the imams of the mosque.
دعوة